PRELIMINARY ASSESSMENT OF DIGESTIVE ENZYMES ON NILE TILAPIA PRODUCTION AND EFFECT ON ITS LIVER MORPHOLOGY - ADEOYE, A.A (Nigerian Journal of Fisheries, 2020)
A feeding trial was done to assess the dietary effects of digestive enzymes on Nile tilapia (Oreochromis niloticus) production and their effects on its liver morphology. Each of the tilapia treatments (38.74±0.51 g fish-1) were dispensed each experimental diet; one as a control and others were supplemented with phytase, protease, and carbohydrase at 0.03 %, 0.02 %, and 0.03 %, respectively. After six weeks, the fish fed the phytase supplemented diet had higher final body weight and SGR (P < 0.05) than fish fed the control and protease supplemented diets. In terms of feed conversion and protein efficiency ratios, the fish fed phytase and carbohydrase diets performed better than the control group (P < 0.05). The fish liver tissue revealed that cellular structure had a regular arrangement with clear boundaries without any severe degradation in any of the dietary treatments. The hepatic density was higher (P < 0.05) in the fish fed protease and carbohydrase supplemented diets than those fed the phytase diet, though not different from the control group. It could be concluded therefore that dietary supplementation of phytase and carbohydrase at the current dosage can improve the performance and nutrient utilisation of Nile tilapia (O. niloticus) without deleterious effect on liver morphology.